Assessing tools for sizing pressure relief devices: Dynamic conditions - Arian Issel (2022)
This thesis deals with the comparison of various commercial software tools with the task to evaluate their suitability for TÜV SÜD to replace the state-of-the-art emergency relief system sizing procedure. As proper relief system sizing is of great importance regarding safety, TÜV SÜD is interested in an improvement of this procedure with the help of specialized software. After an introduction and a theoretical background, the thesis presents requirements for the different software tools. Afterwards, every software is introduced and revised regarding the fulfillment of the requirements. After revision of the requirements, standard emergency relief systems design scenarios are applied to each software (both steady state and dynamic) and compared to the current calculation technique. The software tools evaluated in this thesis are SuperChems, FlowNex, ChemCad SafetyNet and ProSar. If applicable, dynamic simulations are applied and the results are presented and discussed. To provide a better understanding on how the software works, detailed exampled are worked out in the appendix in addition to the standard design scenarios in previous chapters. The thesis closes with a discussion about every software and an outlook.
Keywords: Druckentlastung; Verfahrenstechnik; Dimensionierung; device